Greek City: War, Art And 3d-Visualization - Silnov, Alexander V. (Acta Archaeologica Lodziensia, 2019)
The article discusses issues related to the evolution and development of the Greek polis. The types of urban planning and architectural-spatial elements of the ancient city are analyzed. As a graphical application are presented some computer reconstructions performed at the Department of History and Theory of Architecture at St. Petersburg State University of Architecture and Civil Engineering.